Influence of Foreign DNA Introduction and Periplasmic Expression of Recombinant Human Interleukin-2 on Hydrogen Peroxide Quantity and Catalase Activity in Escherichia coli - Lena Mahmoudi Azar; Elnaz Mehdizadeh Aghdam; Farrokh Karimi; Babak Haghshenas; Abolfazl Barzegari; Parichehr Yaghmaei; Mohammad Saeid Hejazi (Advanced Pharmaceutical Bulletin, 2013)
Purpose: Oxidative stress is generated through imbalance between composing and decomposing of reactive oxygen species (ROS). This kind of stress was rarely discussed in connection with foreign protein production in Escherichia coli. Effect of cytoplasmic recombinant protein expression on Hydrogen peroxide concentration and catalase activity was previously reported. In comparison with cytoplasm, periplasmic space has different oxidative environment. Therefore, in present study we describe the effect of periplasmic expression of recombinant human interleukin-2 (hIL-2) on H2O2 concentration and catalase activity in Escherichia coli and their correlation with cell growth. Methods: Having constructed pET2hIL2 vector, periplasmic expression of hIL-2 was confirmed. Then, H2O2 concentration and catalase activity were determined at various ODs. Wild type and empty vector transformed cells were used as negative controls. Results: It was shown that H2O2 concentration in hIL-2 expressing cells was significantly higher than its concentration in wild type and empty vector transformed cells. Catalase activity and growth rate reduced significantly in hIL-2 expressing cells compared to empty vector transformed and wild type cells. Variation of H2O2 concentration and catalase activity is intensive in periplasmic hIL-2 expressing cells than empty vector containing cells. Correlation between H2O2 concentration elevation and catalase activity reduction with cell growth depletion are also demonstrated. Conclusion: Periplasmic expression of recombinant hIL-2 elevates the host cell’s hydrogen peroxide concentration possibly due to reduced catalase activity which has consequent suppressive effect on growth rate.